Vitamin C use as a preventive measure against COVID-19 - Jhofre Vinicio Prado Quilambaqui; Daniela Monserrath López Hoyos; Heidy Aylin Banda Marcillo (Medisur)
The SARS-CoV2 (COVID-19) disease caused a global health crisis. The World Health Organization shows high morbidity and mortality figures and it is essential to delve into the epidemiological and clinical aspects of diagnosis and treatment to face and defeat this disease. Some researchers have shown that the use of vitamin C, both from food as well as oral or intravenous vitamin supplements, has a positive effect on the body. The potential effect of vitamin C is the reduction of lung inflammation that could play a key role in lung injury caused by coronavirus infection.